2018
DOI: 10.1111/jan.13724
|View full text |Cite
|
Sign up to set email alerts
|

A systematic mixed studies review of women's experiences of perineal trauma sustained during childbirth

Abstract: Perineal trauma can have a negative impact on psychological/emotional wellbeing, however the literature is conflicted and in need of clarification. Future research should clearly describe the perineal status of the women in the sample, use validated measures and consider the timing of such measures. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 54 publications
2
12
0
4
Order By: Relevance
“…Health care providers seemingly strived for normalization of women's symptoms, as described in the category "Burdened by normality". A similar theme, "Normalization and feeling dismissed", was identi ed in a systematic mixed study review of women's experiences of perineal trauma sustained during childbirth [16]. One of the studies included in the review [8] explored the disconnect between expectations and reality for women in the postpartum period under the theme "The fractured fairytale".…”
Section: Discussionmentioning
confidence: 99%
“…Health care providers seemingly strived for normalization of women's symptoms, as described in the category "Burdened by normality". A similar theme, "Normalization and feeling dismissed", was identi ed in a systematic mixed study review of women's experiences of perineal trauma sustained during childbirth [16]. One of the studies included in the review [8] explored the disconnect between expectations and reality for women in the postpartum period under the theme "The fractured fairytale".…”
Section: Discussionmentioning
confidence: 99%
“…This opinion is consistent with a systematic mixed studies review about perineal trauma which reported on the theme 'normalization and feeling dismissed', which means women's health problems are regarded as a normal consequence of childbirth and that their questions were left unanswered by health professionals. 51 Some studies reported women felt frustrated and abandoned because they were 'dismissed by health care providers'. 52 53 The study also raised the interplay between physical injury and pain, the societal expectations that this was normal, and the women's personal anxieties about the anticipated damage to their genitalia and anticipated pain with sex.…”
Section: Discussionmentioning
confidence: 99%
“…This opinion is consistent with a systematic mixed studies review about perineal trauma which reported on the theme ‘normalization and feeling dismissed’, which means women’s health problems are regarded as a normal consequence of childbirth and that their questions were left unanswered by health professionals. 51 Some studies reported women felt frustrated and abandoned because they were ‘dismissed by health care providers’. 52 53 …”
Section: Discussionmentioning
confidence: 99%
“…Transcripts were then analyzed with inductive and deductive qualitative content analysis, 44 a commonly used method of qualitative data analysis. [45][46][47] Three independent coders analyzed the transcripts. One coder had not been involved previously in the study.…”
Section: Discussionmentioning
confidence: 99%